Study to evaluate the clinicopathological characteristics and prognostic factors in patients of breast carcinoma below 35 years of age (a study of 200 cases) - Dr. Mitsu Vaishnav; Dr. Sameep Garg (Tropical Journal of Pathology and Microbiology, 2019)
Introduction: Breast cancer is one of the most common malignancies among women in most developed and developing regions of the world. In India, breast cancer is the second most common cancer (after cervical cancer). Breast cancer at young age has been reported to have a more aggressive behavior and unfavorable prognosis compared to the older patients. Aims and Objectives: To evaluate prognosis through pathological tumour size, histological grade, mitotic index, lymph node status, distant metastasis and oestrogen & progesterone receptor positivity in young patients ≤ 35 years. Material and Methods: This prospective study was carried out for a period of three years from June 2015 to May 2018. Total of 200 cases of breast carcinoma were studied, out of them patients with ≤35 years were considered as case group and above 35 years of age as control group. Results: Total of 200 cases of breast carcinoma was reported in various age groups in histopathology. Total cases in age group ≤35 years were 28 out of total 200 cases. In age group ≤35 years out of 28 cases, 09 cases showed positive family history, 22 cases showed lymph node metastasis, most common stage of breast carcinoma was stage III, most common histological grade was Grade III and 15 cases were negative for markers ER/PR. Conclusion: Breast cancer is uncommon in young women but it co-relates with a less favorable prognosis. Tumors in younger patients had higher co-morbidity and better screening procedures should be used even in females younger than 35 years of age.